Debate of Ideas and Proceduralization of Knowledge in Physical Education and Sport: A Powerful Vector for Pedagogical Innovation in STAPS - Aboufirass, Radouane (Lembaga Yasin AlSys, 2025)
This study focuses on reflective learning in Physical Education and Sport (PE/Sport), alongside learning by action and observation, and examines how a debate of ideas (socio-cognitive conflict) within a group of students enables the construction of learning through the teacher’s pedagogical mediation. By verbalizing the problems encountered during learning situations and proceduralizing knowledge, students become able to learn autonomously and responsibly through self-management. This expected outcome is consistent with the overarching aims of competency-based pedagogy and the pedagogical orientations of the National Charter for Education and Training, which seek to train citizens capable of developing analytical and reflective skills and the ability to adapt. Control groups were established to allow comparison of outcomes, and at the end of the experiment, students in the experimental groups showed greater progress than those in the control groups. These results confirm the research hypothesis that learning constructed by students themselves through a collective project based on the verbalization of actions and problem-solving is more effective, both for students and for teachers.